Heterologous expression and functional characterization of the homologous fucoidanase from Formosa haliotis - Vo, Thi Dieu Trang; Huynh , Hoang Nhu Khanh; Cao, Thi Thuy Hang; Le, Dinh Hung; Dinh, Thanh Trung; Phan , Thi Hoai Trinh; Ngo , Thi Duy Ngoc; Le, Thi Hoa; Pham, Duc Thinh; Mikkelsen, Maria Dalgaard; Meyer, Anne S. (Vietnam Journal of Marine Science and Technology, 2025)
Fucoidanases, enzymes that catalyze the degradation of fucoidan—a sulfated polysaccharide from brown algae—have garnered increasing attention for their potential in biomedical, pharmaceutical, and food applications. In this study, we report the heterologous expression and functional characterization of Fhf3ΔSPNW, a homologous fucoidanase derived from the marine bacterium Formosa haliotis. A truncated version of the gene was amplified and successfully cloned into the pET31b(+) vector, followed by transformation into Escherichia coli BL21(DE3) for protein expression. The recombinant protein, with a molecular weight of ~52 kDa, was confirmed using SDS-PAGE and Western blot analysis. Purification using Ni-NTA affinity chromatography yielded high-purity enzyme fractions. Functional assays demonstrated that Fhf3ΔSPNW exhibited specific activity against fucoidan from brown seaweed Fucus evanescens, suggesting a preference for substrates with alternating α(1→3)/α(1→4) linkages and moderate sulfation. These findings highlight Fhf3ΔSPNW as a promising candidate for the selective production of bioactive oligo-fucoidans, and contribute to the growing toolbox of homologous fucoidanases for tailored enzymatic applications.